The influence of price, brand image and promotion on the decision to purchase Ventela shoes - Dava Satria Wangsawinangun; Nur' Aeni Nur' Aeni (Institute of Computer Science (IOCS), 2023)
The effect of Price, Brand Image and Promotion on the Purchase Decision of Ventela Shoes. The formulation of the problem in this study is the influence of price, brand image and promotion on the decision to purchase Ventela shoes. This type of research uses a quantitative type. The number of samples is 110 students who study at Pelita Bangsa University. The data used in this study are primary and secondary data, namely the distribution of questionnaires and through Google forms to Pelita Bangsa University students. The research uses the Lisrel data processing application version 8.8. The results of this study are: (1) Price has no effect on Purchasing Decisions, (2) Brand Image has no effect on Purchase Decisions, (3) Promotion has an effect on Purchase Decisions.